Understanding the Contestation of Multi Political Parties in Indonesia Through Nietzsche’s Conflictive-Agonistic Power And Elias’s Figurative Power Conception - Alim Roswantoro (UIN Sunan Kalijaga Yogyakarta, 2019)
Observing the contestation of the political parties in the last two decades in Indonesia encourages us to know the political power they understood and the political power logic they practiced. To disclose the understanding, the paper explores the notion of Nietzsche and Elias on power. Nietzsche’s will to power becomes an immutable basis for an individual to get his power against the others. It confronts individual against other individual is a social-political contest. Individual must use his freedom to rise his strength potentials to win power. The contestation among individuals in the social-political sphere is performed in order to master and rule one another. Nietzsche’s power seems to be conflictive-agonistic. Meanwhile, Elias understands power not by confronting each individual’s strength to others’ ones. Power, for him, exists in the interdependence of individuals. Power is figurative or configurative. The contestation of multi political parties in Indonesia so far, seen from the conception of power by Nietzsche and Elias, showing the conflictive-agonistic power rather than the configurative one.[Mencermati sepak terjang partai-partai politik di Indonesia di Indonesia dalam dua dekade terakhir ini membuat kita bertanya-tanya bagaimana sebenarnya mereka yang terlibat di dalamnya memahami kekuasaan, atau bagaimana sebenarnya logika kekuasaan yang berjalan di dalamnya. Untuk memahaminya, tulisan ini mereview perbincangan filosofis mengenai kekuasaan, terutama dalam pemikiran Nietzsche dan Elias. Kehendak untuk berkuasa Nietzsche memperhadapkan individu dengan individu lain. Untuk berkuasa, individu harus menggunakan kebebasannya untuk mengeluarkan seluruh potensi kekuatannya hingga berada di atas dan mengatasi individu-individu lain. Setiap individu melakukan hal yang sama sebagai pejuang yang ingin memenangkan laga. Kontes antar individu di ruang sosial-politik dilakukan untuk saling mengatasi dan menguasai. Kekuasaan perspektif Nietzsche tampak berkarakter agonistik-konfliktual sementara Elias memahami kekuasaan bukan dengan memperhadapkan kekuatan antar individu. Kekuasaan perspektif Ellias ada dalam interdependensi antar individu. Kekuasaan bersifat figuratif atau konfiguratif. Perhelatan politik multi partai di Indonesia hingga sekarang, dalam perspektif dua corak kekuasaan tersebut, masih memperlihatkan suatu kekuasaan yang agonistik-konfliktual daripada konfiguratif.]